EFEK GEL EKSTRAK HERBA PEGAGAN (Centella asiatica L. Urban) DENGAN GELLING AGENT HIDROKSIPROPIL METHYLCELLULOSE TERHADAP PENYEMBUHAN LUKA BAKAR PADA KULIT PUNGGUNG KELINCI - Tanti Azizah Sujono; Ullya Nur Wahyu Hidayah; T.N. Saifullah Sulaiman (Biomedika, 2014)
Pegagan (Centella asiatica L. Urban) contain saponin asiaticoside, which is a structural protein. The compound plays a role in the wound healing process by the formation of collagen. This research was conducted to determine the effect of wound healing of burns on New Zealand male rabbits using gel extract of Pegagan (Centella asiatica L. Urban) herbs using hydroxypropyl methylcellulose (HPMC) as gelling agent. This research was an experimental with the same subject design, using ve male New Zealand rabbits to test the wound healing of burns, and the backs of each rabbit were divided into six treatment i.e : positive control (Bioplasenton), negative control (no treatment), control HPMC base (no extract), and three formula with herbal extracts of Centella asiatica with a concentration of gelling agent HPMC 8%, 9%, and 10% respectively. Gel was applied to the back of rabbits with the use ± 0.3 grams once daily until the wound diameter equal to zero or until healed. The data was analyzed by one way anava with a 95% confidence level. The result showed that of the gelling agent HPMC concentration effect on the increased the viscosity, and decreased the spreadability and the burn wound healing time is a longer. Gel herb pegagan extract (Centella asiatica L. Urban) with a gelling agent HPMC concentration of 8% (17,60±1,14 days) most effectively heal burns compared to the concentration of 9% (19,40 ±1,14 days) and concentration 10% (20,40±1,14 days).Keywords: Centella asiatica L. Urban, gel, hydroxypropyl methylcellulose, burns.